Geochronology and geochemistry of the high Mg dioritic dikes in Eastern Tianshan, NW China: Geochemical features, petrogenesis and tectonic implications - Li, D.; Zhang, L.; Chen, H.; Hollings, P.; Cao, Mingjian; Fang, J.; Wang, C.; Lu, W. (Pergamon-Elsevier Science Ltd, 2016)
© 2015.Zircon U-Pb ages of high Mg dioritic dikes in the Mesoproterozoic Kawabulake Group in the Eastern Tianshan area, NW China indicate that they were emplaced in the Early Carboniferous at 353-348Ma. The dikes consist of medium-grained plagioclase and hornblende with minor clinopyroxene and trace quartz. They are characterized by intermediate SiO2 (60-62wt.%), low TiO2 (0.63-0.71wt.%), relatively high Al2O3 (15.1-15.8wt.%) and MgO contents (3.45-4.15wt.%) with Mg# generally higher than 56 (56-59). The geochemistry of the high Mg diorites suggest they were formed by similar magmatic processes to sanukitoid high Mg Andesites such as those of the Setouchi volcanic belt, Japan. Zircons from the high Mg dioritic dikes have eHf(t) values of -6.8 to +14.5. The dominantly positive values suggest a juvenile source, whereas the small number of negative values suggests mature components were also incorporated into the source. Similarly, the positive eNd(t) values (0 to +2.2) are interpreted to reflect a juvenile source whereas the negative values of (-5.2 to 0) suggest participation of old crustal rocks in the petrogenesis of the diorites. The variable eHf(t) and eNd(t) values suggest that the mature material was assimilated during magma ascent rather than in the mantle wedge which would result in more uniform values. Mass balance calculations suggest that the dioritic dikes were derived from sources composed of approximately 97% juvenile mantle-derived material and 3% sediment. Petrographic, elemental, and isotopic evidence suggest that the dioritic dikes were generated by partial melting of depleted mantle that migrated into the shallow crust where it assimilated older sedimentary rocks of the Mesoproterozoic Kawabulake Group.